Entre bancos e espadas: os bastidores da mediação no sindicato dos bancários do Pará entre 1964 e 1974 - ANDRADE, Cássio Guilherme Franco de (2006)
It addresses the impact of 1 the Banking Reformation in Pará between 1964 and 1974 and the institutionalization of the Authoritarian State for the Military Regimen after-64. The Authoritarian State, exactly with politics of social control and closing politician contributed for a wage freeze, controlling claims and reactions of the workers. With the scene of the Banking Reformation, the banks had that to adapt it the new format of the system with capital increase and more ahead developed a propitious climate the claim to involve the fight of the workers throughout some stages. Fruit of a previous tradition, the experience of present classroom in the practical one of syndical movement assumed the mediation in the negotiations together to the representatives of the State.